Designed to Manipulate: Psychological Design Ethics in the Era of Green Tech - Pande, Sangieta (Global journal of Business and Integral Security, 2026)
Digital technology has been a big part of making people act in a way that is good for the environment, like apps that track emissions and green-commerce interfaces. The persuasive features built into these systems, like nudges, gamification, and emotional triggers, make it hard to tell the difference between ethical influence and psychological manipulation. This research investigates the impact of sustainability-focused digital platforms on user autonomy and trust through persuasive design. The study employed a mixed-methods approach, incorporating survey data, experimental testing, case studies, and expert interviews, to examine whether green-tech experiences empower or exploit individuals. The study introduces a Psychological Design Ethics Framework that delineates openness, empowerment, and fairness as the core principles of ethical digital sustainability.